Inflation rate dispersion and convergence in monetary and economic unions: lessons for the ECB - Axel A. Weber; Günter W. Beck (Goethe University Frankfurt, Center for Financial Studies (CFS), 2005)
Using a set of regional inflation rates we examine the dynamics of inflation dispersion within the U.S.A., Japan and across U.S. and Canadian regions. We find that inflation rate dispersion is significant throughout the sample period in all three samples. Based on methods applied in the empirical growth literature, we provide evidence in favor of significant mean reversion (?- convergence) in inflation rates in all considered samples. The evidence on ?-convergence is mixed, however. Observed declines in dispersion are usually associated with decreasing overall inflation levels which indicates a positive relationship between mean inflation and overall inflation rate dispersion. Our findings for the within-distribution dynamics of regional inflation rates show that dynamics are largest for Japanese prefectures, followed by U.S. metropolitan areas. For the combined U.S.-Canadian sample, we find a pattern of withindistribution dynamics that is comparable to that found for regions within the European Monetary Union (EMU). In line with findings in the so-called 'border literature' these results suggest that frictions across European markets are at least as large as they are, e.g., across North American markets.
urn:nbn:de:hebis:30-23431
Keywords: E31; E52; E58; 330; Inflation Convergence; Deflation; ECB Monetary Policy; EMU; Regional Diversity